2019
DOI: 10.1111/are.14096
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome, enzyme activity and histopathology analysis reveal the effects of high level of dietary carbohydrate on glycometabolism in juvenile golden pompano,Trachinotus ovatus

Abstract: Golden pompano (Trachinotus ovatus) is an important aquaculture species in Chinaand broadly cultivated in Asia-Pacific region. Our previous study found that T. ovatus had a better tolerance to the high level of carbohydrate in diet (360 g/kg) compared to Micropterus salmoides. Present study investigated the tolerance mechanism of T. ovatus to high level of dietary carbohydrate (PH-360 g/kg of corn starch) on transcriptome level using Illumina sequencing compared to optimum level of dietary carbohydrate (PM-240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…A previous study on juvenile largemouth bass (Micropterus salmoides) conducted by Zhang et al (2019) found that marine carnivorous fish have ability to utilize dietary carbohydrate by analysing transcriptome and enzyme activity. Liu et al (2019) obtained similar results in an experiment of juvenile golden pompano (Trachinotus ovatus) by feeding high dietary carbohydrate.…”
Section: Discussionsupporting
confidence: 55%
“…A previous study on juvenile largemouth bass (Micropterus salmoides) conducted by Zhang et al (2019) found that marine carnivorous fish have ability to utilize dietary carbohydrate by analysing transcriptome and enzyme activity. Liu et al (2019) obtained similar results in an experiment of juvenile golden pompano (Trachinotus ovatus) by feeding high dietary carbohydrate.…”
Section: Discussionsupporting
confidence: 55%
“…As a result, R36 had a higher dietary carbohydrate content than R24. Studies suggested that carnivorous fish had low utilization of dietary carbohydrate (Liu et al, 2019; Yang et al, 2018; Zhang et al, 2019), which may be the reason for the lower growth of the R36 group. The study by Shimeno et al (1996) found that a high level of dietary carbohydrate adversely affected fish growth, feed conversion and protein retention.…”
Section: Discussionmentioning
confidence: 99%
“…In our unpublished research on the pearl gentian grouper transcriptomes of the intestine and liver tissues, the transcript annotation rates were 32.64 and 36.58%, respectively. Also, in our published articles on M. salmoides and Trachinotus ovatus, in which the transcriptomes were sequenced by the Illumina 2000 platform, the annotation rates of the transcripts were 52.98% (26,886/50,743) (Zhang et al, 2019) and 43.30% (27,366/62,377) (Liu et al, 2019), respectively. Although the raw data obtained from third-generation sequencing had relatively more error, it can be corrected through the data obtained from next-generation sequencing (Hackl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%